Tobacco Abuse in Adolescents: The Role of Psychosocial Factors (Global Journal of Human-Social Science, 2011)
The present investigation was done to examine the role of anxiety stress family conflict and family control in the determination of adolescents smoking For accomplishing these objectives a sample of 240 students studying in different schools from two districts of Himachal Pradesh Shimla and Solan was taken The age range of the sample was 14-19 years 2x2x2 factorial design was used to study the significance of difference between groups smokers and nonsmokers schools public and private and gender males and females on anxiety stress family conflict and family control Results revealed that smokers irrespective of gender and type of school were significantly higher on anxiety stress family conflict and family control Further on family control the interaction effects of group or school and gender or school have been found to be significant
Keywords: Smoking; Anxiety; Stress; Family Conflict; Family Control; School and Gender